PERAN PERCEIVED DESIRABILITY DALAM MEMEDIASI HUBUNGAN ANTARA ATTITUDE DENGAN ENTREPRENEURIAL INTENTION - Tulipa, Diyah; Sancoko, Aldo Hardi; Rahmawati, Veronika (Media Mahardhika, 2024)
Entrepreneurship is a government program aimed at reducing unemployment and improving welfare. It is also targeted at universities to create independent and entrepreneurial graduates who can become a driving force in running their own businesses and creating jobs for themselves and others. The objective of this study is to assess the entrepreneurial behavior of students in Surabaya who have received entrepreneurship education. The study sample consisted of 103 students selected through purposive sampling based on specific criteria.  The data was analyzed using Smart-PLS software. The results indicate that attitude has a positive and significant impact on perceived desirability, which in turn has a positive and significant impact on entrepreneurial intention. Additionally, attitude has a direct positive and significant impact on entrepreneurial intention, as well as an indirect positive and significant impact through perceived desirability. Perceived Desirability acts as a mediator variable between Attitude and Entrepreneurial Intention. Entrepreneurship is closely linked to planned and actual action. This research model is based on the TPB and SEE models. However, due to limitations in the integration model and this study, the measurement of entrepreneurial behavior is still limited to Entrepreneurial Intention. Therefore, future research should focus on measuring entrepreneurial behavior at the level of direct implementation of entrepreneurial activities  Keywords: attitude, perceived desirability, entrepreneurial intention